What's New in Pediatric and Adolescent Anterior Cruciate Ligament Injuries?. Issue 3 (March 2018) - Dekker, Travis J.; Rush, Jeremy K.; Schmitz, Matthew R.
Abstract : Background: Anterior cruciate ligament (ACL) tears in children and adolescent patients are being diagnosed and treated at an ever-increasing rates. We performed a review of recent literature regarding care of children and adolescent athletes with an ACL injury. Methods: PubMed database was searched for all papers related to treatment of children and adolescents with ACL injuries from October 1, 2012 to September 30, 2015, yielding 114 publications. Results: A total of 59 papers were found to have contributed important new findings. Papers were selected based on new findings in the following categories: epidemiology, anatomy, risk factors, sex disparity, prevention, surgical outcomes, timing and associated pathologies, and rehabilitation and return to sport. Conclusions: Pediatric ACL injuries continue to rise and there are multiple surgical procedures that restore clinical function with good outcomes. Early surgical treatment is favored to prevent concomitant articular injuries. Early return to play can increase risk of reinjury and should be met with caution in this age group. Prevention strategies should be further studied and implemented in hopes of decreasing the incidence of this injury and the long-term potential damage. Level of Evidence: Level 4—titerature review.